Does Sdds Subscription Reduce Borrowing Costs for Emerging Market Economies - Cady, John. (Washington, D.C. : International Monetary Fund, 2004)
Does macroeconomic data transparency-as signaled by subscription to the IMF's Special Data Dissemination Standard (SDDS)-help reduce borrowing costs in private capital markets? This question is examined using detailed data on new issues of sovereign foreign currency-denominated (U.S. dollar, yen, and euro) bonds for several emerging market economies. Panel econometric estimates indicate that spreads on new bond issues declined by about 75 basis points following SDDS subscription.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet